AGRONOMIC PERFORMANCE AND WATER USE EFFICIENCY OF IRRIGATED CACTUS PEAR CULTIVARS - Castro, Igor Nogueira de (2020)
Cactus pear is an alternative for animal feed in the semiarid region, and its productive characteristics can be improved with little irrigation. The objective of this work was to assess the agronomical performance and water use efficiency (WUE) of two cactus pear cultivars subjected to different irrigation water depths and define the best material genetic material for irrigated conditions in the semiarid region of the state of Minas Gerais (MG), Brazil. The experiment was conducted in Montalvânia, MG, during one year (2017-2018) using six treatments consisting of irrigation water depths based on the reference evapotranspiration (ET0) (without irrigation, 15%, 30%, 45%, 60%, and 75% ET0) and two genetic materials (Opuntia ficus-indica Mill. cv. Gigante, and Nopalea cochenillifera Salm-Dyck cv. Miúda). A randomized block design was used, in a with split-plot arrangement consisting of irrigation treatments in the plots and genetic materials in the subplots, with four replications. Growth evaluations were carried out from the third month after planting to the end of the growing cycle. Production variables and WUE were evaluated at the harvest. The irrigation water depths affected the growth variables, significantly (p<0.05). The water depths of 40% to 50% ET0 provided higher fresh and dry matter yields; the cultivar Miúda showed better performance than the Gigante. The WUE was affected by the irrigation water depths; the cultivar Miúda was the best option for the crop.